Environmental crimes in forestry management in Valle del Cauca: environmental legal analysis - Cabrera Suárez, Julio César (DIXI, 2023)
Subject and scope: One of the problems that most affects the environment and human beings is overpopulation, which reduces the possibility of having a better quality of life. The international covenants and agreements that have been entered into have contributed significantly to the creation of an environmental awareness on the part of the people, as well as to the conviction that natural resources are not inexhaustible. Although we have a rich country in terms of its geographical position, biodiversity, irregular topography and tropical climate, unfortunately it has a major deforestation problem that threatens its riches.Characteristics: Biodiversity is important because its various elements and processes are necessary for the preservation of the ecological balance that contributes to human well-being. The 1991 Political Constitution is the first to recognize the ethnic and cultural diversity of the Colombian nation and the great wealth of biodiversity in the country, which is why it is known as “green”.Findings: The 1991 Constitution is one of the most prodigious events in our history. It is the first Constitution that did not arise from an imposition, but from an agreement between Colombians of very different origins and ideologies. It is the Constitution that put Colombia at the forefront of the recognition of rights, whose main objective consisted of creating a regime of legal guarantees of public and private freedoms based on the principle of respect for the dignity of the person, a consecration that made us dream of the political and legal transformation that would guarantee the inviolability of freedoms and human rights, and the fulfillment of the purpose of social justice.
Keywords: forest; natural resources; human beings; environmental legislation; environmental crimes; legal security; environmental education